The Application Of Batak Karo Customary Law In Marriage And Social Life - Tarigan, Agnesia Br; Hasan , Zainudin (Social Sciences Journal, 2025)
The Karo Batak community has a strong customary law system that governs various aspects of social life, including marriage arrangements and community relations. This study aims to analyze the implementation of Karo Batak customary law in the field of marriage (including clan exogamy prohibitions, customary procedures, and sanctions) as well as its role in maintaining social order and the cultural identity of the community. The study employs a qualitative method with a literature study approach and normative analysis of customary and socio-cultural law sources. The results indicate that Karo Batak customary law continues to function as a living law that is actively observed by the community, in line with the theories of Receptie, Receptie Exit, and Living Law. Although modernization and migration bring changes in values and challenges to the preservation of customs, Karo customary law remains an important regulator of moral, social, and cultural life within the community.